PERFORMA PELELEHAN ES PADA BENTUK ES YANG BERBEDA (Performance of Diffrent Ice-Forms Melting Process) - Aprilia Putri Kusumah; Yopi Novita; Deni A. Soeboer (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2015)
ABSTRACTIce as a cooling medium in the handling of fresh fish is widely used. Information about the rate of temperature change and the rate of melting of ice in the fish storage box is not available. Therefore, this research needs to be conducted to determine the ability of different forms of ice to decrease the temperature of the ice box where they are placed. The objectives of this research are to calculate the rate of ice melting and the rate of temperature change in the box that contains the bulk ice and crushed ice, and compare the ability of bulk ice and crushed ice to cool temperature inside the storage box fish. Experimental method was applied in this research, which data collection consisted of a total volume of ice melted and the temperature in the box per unit time. The research results showed that the bulk ice has the ability to cool the space they occupy much faster when compared with crushed ice. In addition, bulk ice melt faster when compared with crushed ice.Keywords: ice, the rate of melting of ice, the rate of temperature change-------ABSTRAKPenggunaan es sebagai media pendinginan dalam penanganan ikan segar merupakan yang paling umum digunakan. Informasi tentang laju perubahan suhu dan laju pelelehan es di dalam boks penyimpanan ikan belum tersedia. Oleh karena itu, penelitian ini perlu dilakukan untuk mengetahui kemampuan es dalam bentuk yang berbeda untuk menurunkan suhu boks dimana es tersebut ditempatkan. Tujuan penelitian ini adalah menghitung laju pelelehan es dan laju perubahan suhu di dalam boks yang berisi es curah dan es hancuran serta membandingkan kemampuan es curah dan es hancuran untuk mendinginkan suhu di dalam boks tempat penyimpanan ikan. Pengambilan data dilakukan terhadap jumlah volume lelehan es dan suhu di dalam boks per satuan waktu dengan menggunakan metode experimental. Berdasarkan hasil penelitian diketahui bahwa es curah memiliki kemampuan untuk mendinginkan ruang yang ditempatinya lebih cepat jika dibandingkan dengan es hancuran. Selain itu, es curah lebih cepat meleleh jika dibandingkan dengan es hancuran.Kata kunci: es, laju pelelehan es, laju perubahan suhu